2020
DOI: 10.3389/fonc.2020.00326
|View full text |Cite|
|
Sign up to set email alerts
|

Gastric Cancer Cell-Derived Exosomal microRNA-23a Promotes Angiogenesis by Targeting PTEN

Abstract: Hypoxia-exposed lung cancer-released exosomal microRNA-23a (miR-23a) has been shown to enhance angiogenesis as well as vascular permeability, contributing to the close correlation between exosomal miR-23a and tumorigenesis. The current study aimed to investigate whether gastric cancer (GC) cell-derived exosomal miR-23a could induce angiogenesis and to elucidate the potential mechanisms associated with the process. Differentially expressed miRNAs in GC were initially screened from the Gene Expression Omnibus da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…The same study demonstrated that the upregulation of another miRNA, miR-616-3p, in GC tissues resulted in the downregulation of PTEN and PI3K/AKT/mTOR pathway activation through PTEN, which then contributed to EMT and angiogenesis [ 23 ]. A second study confirmed the relevance of miR-23a, and a third study confirmed the relevance of miR-616-3p in GC [ 60 , 70 ]. In the study by Du et al, miR-23a was highly expressed in GC tissues, cells, and GC cell-derived exosomes.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The same study demonstrated that the upregulation of another miRNA, miR-616-3p, in GC tissues resulted in the downregulation of PTEN and PI3K/AKT/mTOR pathway activation through PTEN, which then contributed to EMT and angiogenesis [ 23 ]. A second study confirmed the relevance of miR-23a, and a third study confirmed the relevance of miR-616-3p in GC [ 60 , 70 ]. In the study by Du et al, miR-23a was highly expressed in GC tissues, cells, and GC cell-derived exosomes.…”
Section: Resultsmentioning
confidence: 80%
“…In the study by Du et al, miR-23a was highly expressed in GC tissues, cells, and GC cell-derived exosomes. This miRNA was demonstrated to promote angiogenesis via the repression of PTEN in a co-culture system [ 70 ]. The role of miR-616-3p as a promoter of angiogenesis via the PTEN/AKT/mTOR pathway in GC has also been confirmed in the study by Wu et al [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, miR-130a from gastric cancer cells-derived exosomes can enter vascular cells and target C-MYB, a transcription factor of angiogenesis, to promote angiogenesis and tumor growth [ 56 ]. MiR-23a carried by GC cells-derived exosomes can be used by vascular cells and suppress the expression of a well-known tumor suppressor gene, PTEN to promote angiogenesis [ 57 ]. These exosomal RNAs from TDEs can target vascular cells and promote angiogenesis though expression alternation of transcription factor or tumor suppressor gene.…”
Section: Role Of Exosomal Rna In the Initiation And Development Ofmentioning
confidence: 99%
“…The growth and metastasis of malignant tumors depend on the formation and dilation of blood vessels (95). Exosomes from various tumors, such as breast cancer (15), colorectal cancer (96), gastric cancer (97), and lung cancer (80), have been shown to play an important role in promoting angiogenesis. It should be noted that the exact mechanism of exosome-driven angiogenesis is not clear, and the angiogenic characteristics of exosome cargoes from different tumor cells vary widely (98).…”
Section: Effect Of Exosomes On Tc Angiogenesismentioning
confidence: 99%